Risk Factors for Child Mortality in the Kassena-Nankana District of Northern Ghana: A Cross-Sectional Study Using Population-Based Data - Michael N. K. Babayara; Bright Addo (Scientifica)
Child mortality continues to be a major public health problem in Ghana, especially in northern Ghana where child survival rates are among the lowest. Though strategies are in place to address it, progress made is unsatisfactory and the Sustainable Development Goal 3 risks being missed. This makes the reexamination of the risk factors for child mortality crucial as results will aid in the modification of existing strategies aimed at addressing the problem. This study was a population-based case control study utilizing data (2007–2011) from the Demographic Surveillance System database of the Navrongo Health Research Center. Cases and controls were selected from the database and analysed unmatched. Cases were children who died before age five and controls were live children within the same year group. Univariate and bivariate analyses were performed using STATA (v13). The results revealed the main causes of death in the area to include malaria, diarrhoeal diseases, respiratory infections, and malnutrition. Mother’s age at birth, mother’s educational level, and mother’s household socioeconomic status were significantly related to child mortality. On the basis of these results, we conclude that the known risk factors for child mortality in the Kassena-Nankana district have not changed much over the years. Current child survival strategies therefore need to be evaluated and modified where necessary to yield desired results.